School literacy in English language class: a critical reading pedagogical proposal - Novelli, Josimayre; Jung, Neiva Maria; de Castro, Elaine (BELT - Brazilian English Language Teaching Journal, 2018)
Teaching a Foreign Language (FL) in Basic Education has among one of its goals contributing to the learner’s singular experience of building meaning by a discursive basis domain (Brasil, 1998), by means of reading and writing activities that promote his engagement in varied social practices and his formation as a citizen (Schlatter, 2009). This way, it’s presented a reading activity to Elementary School students based in Critical Reading (CR) and literacy as social practice (Street, 2014). It is started from reading as a process, proposing steps to achieve it (pre-reading, while-reading e post-reading), which involve previous knowledge of the text issue, text comprehension and interpretation and the development of the learner’s criticism through the text, respectively. Considering this proposal, it’s expected to emphasize the importance of CR to increase the learners’ participation in literate social practices, contributing to the formation of a critical reader and a citizen.